“What the Fuck is the Point of Unpacking?”: Perceptions of Residential Transitions Among People with Histories of Residential Instability - Czechowski, Konrad (Université d'Ottawa / University of Ottawa, 2018)
This study examined the perceptions of housing transitions of individuals with histories of residential instability. Participants were recruited from the Health and Housing in Transition study (HHiT), a longitudinal multi-city Canadian study tracking the health and housing of 1,192 participants over a 5-year period. Twenty-two participants from Ottawa were recruited from the larger study to participate in the present study. Participants were interviewed using a semi-structured interview guide about their experiences of housing transitions (moves from one housing situation to another). A general inductive method for the analysis of qualitative data was used to examine participants’ perceptions of their transitions. Findings suggest that participants experienced feelings of disconnection from their housing situations. Their transitions were characterized as chaotic and initiated by factors outside of their control. Participants attributed their transitions to factors such as interpersonal issues, substance use, financial issues, safety concerns, and pests. The present study emphasizes the complexity of participants’ precarious housing situations and the multifactorial nature of their residential instability.
Keywords: Residential Instability; Housing; Homelessness